Diurnal blood pressure profile and coronary atherosclerosis extent are related to cardiovascular complications - Marcin Wirtwein; Marcin Gruchala; Wojciech Sobiczewski (Blood Pressure, 2017)
The aim of this study was to assess the relationship between 24 h blood pressure (BP) profile, extent of significant coronary artery stenosis, confirmed by coronary angiography, and cardiovascular events in patients with coronary artery disease. Coronary angiographies were performed for all included subjects and significant coronary artery stenosis was considered as ≥ 50% stenosis by atherosclerotic plaque. Twenty-four-hour ambulatory BP monitoring was performed. Major advanced cardiovascular events (MACE) included revascularization, cardiovascular mortality, total mortality, acute coronary syndromes and stroke. BP analysis revealed higher night-time systolic blood pressure (SBP) values in patients with three or more significant coronary artery stenoses than in those without significant stenosis (120.7 ± 16.4 vs 116.7 ± 14.3 mmHg, p < 0.001), lower night-time SBP dip in patients with three or more significant coronary artery stenoses than in those without significant stenosis (5.7 ± 3.2 vs 7.4 ± 6.8 mmHg, p < 0.001) and lower night-time diastolic blood pressure dip in patients with three or more significant stenoses than in patients without significant stenosis (9.4 ± 7.4 vs 11.9 ± 7.4 mmHg, p < 0.001). Night-time SBP values, night-time/daytime SBP dip and extent of significant coronary artery stenosis were risk factors for MACE, revascularization and cardiovascular mortality. In conclusion, the study shows that advanced coronary artery disease is related to blunted night-time BP dipping and cardiovascular complications.